Type I interferons augment regulatory T cell polarization in concert with ancillary cytokine signals - Eskandari, Siawosh K.; Allos, Hazim; Safadi, Jenelle M.; Sulkaj, Ina; Sanders, Jan S. F.; Cravedi, Paolo; Ghobrial, Irene M.; Berger, Stefan P.; Azzi, Jamil R. (Frontiers in Transplantation, 2023)
In the transplant community, research efforts exploring endogenous alternatives to inducing tolerogenic allo-specific immune responses are much needed. In this regard, CD4+FoxP3+ regulatory T cells (Tregs) are appealing candidates due to their intrinsic natural immunosuppressive qualities. To date, various homeostatic factors that dictate Treg survival and fitness have been elucidated, particularly the non-redundant roles of antigenic CD3ζ/T-cell-receptor, co-stimulatory CD28, and cytokine interleukin (IL-)2 dependent signaling. Many of the additional biological signals that affect Tregs remain to be elucidated, however, especially in the transplant context. Previously, we demonstrated an unexpected link between type I interferons (IFNs) and Tregs in models of multiple myeloma (MM)—where MM plasmacytes escaped immunological surveillance by enhancing type I IFN signaling and precipitating upregulated Treg responses that could be overturned with specific knockdown of type I IFN signaling. Here, we elaborated on these findings by assessing the role of type I IFN signaling (IFN-α and -β) on Treg homeostasis within an alloimmune context. Specifically, we studied the induction of Tregs from naïve CD4 T cells. Using in vitro and in vivo models of murine skin allotransplantation, we found that type I IFN indeed spatiotemporally enhanced the polarization of naïve CD4 T cells into FoxP3+ Tregs. Notably, however, this effect was not independent of, and rather co-dependent on, ancillary cytokine signals including IL-2. These findings provide evidence for the relevance of type I IFN pathway in modulating FoxP3+ Treg responses and, by extension, stipulate an additional means of facilitating Treg fitness via type I IFNs.